Consequences of inhibition of mixed‐layer deepening by the West India Coastal Current for winter phytoplankton bloom in the northeastern Arabian Sea. Issue 9 (5th September 2016) - Vijith, V.; Vinayachandran, P. N.; Thushara, V.; Amol, P.; Shankar, D.; Anil, A. C.
Abstract: The intense winter phytoplankton bloom during November–February in the northeastern Arabian Sea (NEAS) was thought, until recently, to be controlled only by a convective deepening of the mixed layer (ML) owing to cool and dry northeasterlies. But a recent study has shown that the deepening of the ML in the southern NEAS is inhibited by the poleward advection of low‐salinity water from the south by the West India Coastal Current (WICC). Using an Ocean General Circulation Model coupled with an ecosystem model, we investigate the consequences of the inhibition of mixed‐layer deepening for winter phytoplankton bloom in the NEAS. We show that, during the winter monsoon, the shallow ML inhibits the entrainment of nutrients in the southern NEAS. Strong (weak) positive nitrate tendency in the northern (southern) NEAS seen in the model during the winter monsoon is maintained by strong (weak) entrainment. As a result, the chlorophyll integrated to 200 m depth from the surface is lower in the southern NEAS than in the northern NEAS. The inhibition of mixed‐layer deepening in the south affects the size‐based distribution of small and large phytoplankton, nutrient limitation terms and growth rate, and their elemental composition. The WICC, which inhibits the deepening of the ML and affects the winter bloom in the NEAS, is driven by coastal Kelvin waves generated by remote winds. This paper demonstrates a mechanism by which remotely forced coastal Kelvin waves impact the biology in the north Indian Ocean. Key Points: West India Coastal Current inhibits entrainment of nutrients in the northeastern Arabian Sea Chlorophyll is lower in the southern part of the northeastern Arabian Sea compared to the northern part Evidence of coastal Kelvin waves influencing biology in the north Indian Ocean